Thermal water structure in the North-West Pacific and role of wind forcing and advection in its forming - Nickolay S. Vanin (Известия ТИНРО, 2017)
Two basic types of vertical thermal structure are defined in the North-West Pacific on the data obtained in CTD survey conducted from May 29 to July 9, 2013 . One of them prevailed in the coastal areas of the Bering Sea and at East Kamchatka where the depth of winter convection was 160-200 m and even more. The other extended over the open ocean with lesser depth of convection as 90-130 m. Their difference in the cold subsurface layer thickness is analyzed in relation with temporal variations of the sea surface temperature and wind stress during preceding winter. The wind forcing contributes to deepening of winter convection in the coastal areas because of the shoreward Ekman transport but induces mostly horizontal advection in the open ocean. The wind-driven flows promote additional cooling in the subsurface layer in the western Bering Sea and major part of the NW Pacific, except the Alaska Stream area where they cause a warming in this layer. The warm intermediate layer in the whole region is supported mainly by westward advection of relatively warm water in the Alaska Stream and partially by the compensatory flow from the south that balances the Ekman transport in the upper layers.